Alphataxin, an Orally Available Small Molecule, Decreases LDL Levels in Mice as a Surrogate for the LDL-Lowering Activity of Alpha-1 Antitrypsin in Humans - Bristow, Cynthia L.; Winston, Ronald (Frontiers in Pharmacology, 2021)
The abundant blood protein α1-proteinase inhibitor (α1PI, Αlpha-1, α1-antitrypsin, SerpinA1) is known to bind to the active site of granule-associated human leukocyte elastase (HLE-G). Less well known is that binding of α1PI to cell surface HLE (HLE-CS) induces lymphocyte locomotion mediated by members of the low density lipoprotein receptor family (LDL-RFMs) thereby facilitating LDL clearance. LDL and α1PI were previously shown to be in negative feedback regulation during transport and clearance of lipoproteins. Further examination herein of the influence of α1PI in lipoprotein regulation using data from a small randomized, double-blind clinical trial shows that treatment of HIV-1-infected individuals with α1PI plasma products lowered apolipoprotein and lipoprotein levels including LDL. Although promising, plasma-purified α1PI is limited in quantity and not a feasible treatment for the vast number of people who need treatment for lowering LDL levels. We sought to develop orally available small molecules to act as surrogates for α1PI. Small molecule β-lactams are highly characterized for their binding to the active site of HLE-G including crystallographic studies at 1.84 Å. Using high throughput screening (HLE-G inhibition, HLE-CS-induced cellular locomotion), we show here that a panel of β-lactams, including the LDL-lowering drug ezetimibe, have the capacity to act as surrogates for α1PI by binding to HLE-G and HLE-CS. Because β-lactams are antibiotics that also have the capacity to promote evolution of antibiotic resistant bacteria, we modified the β-lactam Alphataxin to prevent antibiotic activity. We demonstrate using the diet-induced obesity (DIO) mouse model that Alphataxin, a penam, is as effective in lowering LDL levels as FDA-approved ezetimibe, a monobactam. Non-antibiotic β-lactams provide a promising new therapeutic class of small molecules for lowering LDL levels.